The Singapore Tat2 Show 2010. - Ip, Wai Yin. (2010)
The planning and execution of PR activities for Singapore's second Tat2 Show held at Singapore Expo from 8-10 January 2010. Part of the PR campaign will also be on shifting the public's perception on tattoos, which traditionally have been associated with negative stereotypes and deviance, to one of an art form and an appreciation for their aesthetic value. This paper is based on the public relations (PR) campaign of the Singapore Tat2 Show 2010 (STS2010), conceptualized and executed by our group. The primary objectives of the campaign is to create awareness and drive traffic to the show, but as tattoos are largely misunderstood and marginalized by society, the success of STS2010 depended on breaking negative stereotypes and gaining acceptance. Drawing on the findings of our research, related literature and relevant theories, we identified media opportunities to put together a strategic PR campaign for STS2010. Central to the campaign is communicating real human interest stories and dispelling myths about the tattoo community. This paper will examine and discuss how our PR campaign overcame social resistance and an unfavourable media landscape by utilizing online media and engaging the public to create dialogue and effect change.